3D modeling using Autodesk 3ds Max with rendering view - Samanta, Debabrata 1987- (Advances in web technologies and engineering (AWTE) book series, 2022)
This book guides you through the difficulty of mastering one of the most sophisticated computer programs ever created by concentrating on the aspects of the program that you need to know in order to create outstanding architectural visualisations.